Analisis Faktor Penyebab Berkurangnya Upacara Pernikahan Shinzen Kekkon di Jepang, Khususnya Daerah Kansai - Novianti, Nalti; Dianto, Edi (Lingua Cultura, 2008)
Modernization era has left some particular part on traditional ceremony because it is unpractice reason, like take too much time. It also happens on the wedding ceremony wich has many customs and tradition. One of Japanese wedding tradition is shinzen kekkon, this wedding ceremony is held for Shinto’s beliver. Article explores how is Japanese young generation opinion about their wedding ceremony, besides their knowledge about every part of the ceremony. On conclusion part, it is known that Japanese tradition has spirant in its process.